2019
DOI: 10.1002/chem.201903377
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Catalyzed Cross‐Coupling Reactions: An Overview of Design Strategies, Mechanistic Studies, and Applications

Abstract: Transition-metal-catalyzed cross-couplingr eactions are central to many organic synthesis methodologies. Traditionally,P d, Ni, Cu, and Fe catalysts are used to promote these reactions. Recently,m any studies have showedt hat both homogeneous and heterogeneous Au catalysts can be used for activating selective cross-coupling reactions.H ere, an overview of the past studies, current trends, andf uture directions in the field of gold-catalyzed coupling reactions is presented.D esign strategiest oa ccomplish selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
72
0
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(88 citation statements)
references
References 490 publications
(1,569 reference statements)
4
72
0
12
Order By: Relevance
“…For example, none of these methods allow to assemble richly decorated small molecules in the presence of C−iodine bonds, which owing to their pronounced halogen bonding are receiving increasing interest in medicinal and materials chemistry . In this context, oxidative gold catalysis has emerged as a powerful alternative to construct Csp2 –Csp2 bonds in the presence of aromatic C−halogen, including C−I bonds via the coupling of Ar−FG with ArH (see Figure ) . However, intramolecular competitions of for example, C−Bpin vs. C−SiMe 3 or C−GeR 3 vs. C−SiR 3 functionalizations are—with the exception of ArH=indole and ArF n —not yet possible for a wide range of substrates due to incompatibilities with the strong stoichiometric oxidant that is mechanistically necessary to re‐oxidize Au I to Au III .…”
Section: Figurementioning
confidence: 99%
“…For example, none of these methods allow to assemble richly decorated small molecules in the presence of C−iodine bonds, which owing to their pronounced halogen bonding are receiving increasing interest in medicinal and materials chemistry . In this context, oxidative gold catalysis has emerged as a powerful alternative to construct Csp2 –Csp2 bonds in the presence of aromatic C−halogen, including C−I bonds via the coupling of Ar−FG with ArH (see Figure ) . However, intramolecular competitions of for example, C−Bpin vs. C−SiMe 3 or C−GeR 3 vs. C−SiR 3 functionalizations are—with the exception of ArH=indole and ArF n —not yet possible for a wide range of substrates due to incompatibilities with the strong stoichiometric oxidant that is mechanistically necessary to re‐oxidize Au I to Au III .…”
Section: Figurementioning
confidence: 99%
“…Gold (Au) catalyzed reactions have emerged as a key source for carrying out unprecedented cycloisomerization reactions for the past few decades due to the propensity of gold to bond with heteroatoms like -O, -N, -S [1] and has vast number of applications [2]. Au has a propensity to act as a soft and carbophilic Lewis acid and to activate C-C πbonds.…”
Section: Introductionmentioning
confidence: 99%
“…The success of the application of aryldiazoniums alts in the oxidative addition of Au I came alongw ith the development of photoredox catalysis. [14,15] The mechanistic studies carried out so far indicate that aryl radicals are involvedinthese processes. Initially,b oth light and ap hotosensitizer wereu sed to generate the aryl radicals, but later,i tw as observed that in some instances the photosensitizer was not necessary and that even nucleophiles, bases,o rs imple heatinga re enough to generate aryl radicals (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%